2008
DOI: 10.1073/pnas.0801539105
|View full text |Cite
|
Sign up to set email alerts
|

Cluster reactivity experiments: Employing mass spectrometry to investigate the molecular level details of catalytic oxidation reactions

Abstract: Mass spectrometry is the most widely used tool in the study of the properties and reactivity of clusters in the gas phase. In this article, we demonstrate its use in investigating the molecular-level details of oxidation reactions occurring on the surfaces of heterogeneous catalysts via cluster reactivity experiments. Guided ion beam mass spectrometry (GIB-MS) employing a quadrupole-octopolequadrupole (Q-O-Q) configuration enables mass-selected cluster ions to be reacted with various chemicals, providing insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
67
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 71 publications
4
67
1
2
Order By: Relevance
“…One valuable approach employs the use of clusters whose chemistry can be used to follow the course of reactions influenced by various reactive centers/defect sites, and the present invited perspective focuses on past developments and future prospects in this area [2,5,[7][8][9][10]. While acquiring reproducible defect sites for the purpose of elucidating their influence on the course of catalytic reactions is an arduous task, it is a relatively straight forward procedure to recreate and conduct repetitive studies on model clusters which mimic specific reaction centers.…”
Section: Introductionmentioning
confidence: 99%
“…One valuable approach employs the use of clusters whose chemistry can be used to follow the course of reactions influenced by various reactive centers/defect sites, and the present invited perspective focuses on past developments and future prospects in this area [2,5,[7][8][9][10]. While acquiring reproducible defect sites for the purpose of elucidating their influence on the course of catalytic reactions is an arduous task, it is a relatively straight forward procedure to recreate and conduct repetitive studies on model clusters which mimic specific reaction centers.…”
Section: Introductionmentioning
confidence: 99%
“…The Al 13 cluster does not show any reactivity with oxygen, while other neighboring clusters did. Structure and reactivity of specific Al clusters such as Al 12 , Al 16 , Al 17 , and Al 18 have been extensively explored by Castleman and Khanna. 6 Magic-numbered silver clusters formed by matrix-assisted laser desorption mass spectrometry were reported by Kéki et al 7 Apart from monometallic clusters, they also reported bimetallic Ag-Au clusters.…”
Section: Introductionmentioning
confidence: 99%
“…15 Bridgeman and Cavigliasso investigated the structure and bonding in [W 10 O 32 ] nisopolyanions theoretically. 16 Various kinds of metal-carbon cage clusters were explored in great detail by Guo et al 17 Molecular level details of small WO clusters on oxidative catalysis have been reported by Johnson et al 18 recently. Rothgeb et al 19 reported the unusual reactivity of small anionic WO clusters with H 2 O and D 2 O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some metal ions in H 2 O clusters suffer charge reduction, whereas others show different types of electron and ion solvation. Bulk W n O 3n catalyzes the oxidation of propene to propene oxide and CO to CO 2 (9). In this reaction, gaseous W n O 3n ϩ species of selected n values exhibit enhanced activity and selectivity, indicating a radical oxygen center (W-O•) mechanism.…”
mentioning
confidence: 99%